(untitled) (Economic and Political Thought, 2019)
The analysis presented in the article aims to determine the place and role of the Republic of Austria in the European Union. It shows the beginning of this country’s membership of the EU and the political crisis of the early 2000 after the formation of the ÖVP and FPÖ coalition at the federal government level, which was reflected in the imposition of political sanctions by the other EU states. The analysis covers Vienna’s stand on the prospects of the EU enlargement over the period of the last two decades. The article also presents the situation of this state against the background of the Common Foreign and Security Policy (CFSP), the relationship with NATO and a discussion on the so-called “Öxit”, i.e. the prospect of Austria’s withdrawal from the European Union. The article also shows Austrian society’s attitude towards selected aspects of the European integration as well as the influence of contemporary crises in the EU on the domestic and international situation of this Mid-European state.